Persepsi Orang Tua Dengan Profesi Petani Terhadap Perkembangan Anak Usia Dini - Hayatul Mahmudah; Moh. Fikri Tanzil Mutaqin; Novita Sari (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to describe the perspectives of parents who work as farmers regarding early childhood development within the context of agrarian community life. Early childhood is a critical phase of rapid development that requires consistent care, stimulation, and nurturing. However, farmer parents often face limitations in time, knowledge, and access to information needed to support optimal child growth. This research adopts a descriptive qualitative approach using in-depth interviews, observations, and documentation involving three farming parents from a rural area in Lampung. The findings reveal that parental understanding stems from daily experiences and traditional values. Despite limited resources, parents demonstrate genuine concern for their children’s education and character. They employ simple yet meaningful parenting strategies and creatively overcome challenges such as the lack of learning media and limited time. The study concludes that parenting quality is not solely determined by educational background or profession, but by awareness, emotional involvement, and core family values that guide their actions